2013
DOI: 10.1017/jfm.2013.278
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional modelling of high-Reynolds-number shear flows incorporating constraints from the Navier–Stokes equation

Abstract: A new approach to model order reduction of the Navier-Stokes equations at high Reynolds number is proposed. Unlike traditional approaches, this method does not rely on empirical turbulence modeling or modification of the Navier-Stokes equations. It provides spatial basis functions different from the usual proper orthogonal decomposition basis function in that, in addition to optimally representing the training data set, the new basis functions also provide stable and accurate reduced-order models. The proposed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
157
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 46 publications
4
157
0
Order By: Relevance
“…41 Having defined an acceptable number of modes, a Galerkin system of evolution equations is written for the modes in terms of advective and dissipative terms, with the latter modeled to prevent excessive energy build-up (some form of cascade is required). Approaches are inspired by an eddy-viscosity approach, 41 with more advanced closures incorporating linear approximations to the nonlinear terms 67 or nonlinear interactions directly, 68 and comparative analyses demonstrating the utility of these more advanced formulations. 42 While dyadic wavelet modes are locally correlated at singularities (providing the basis for multifractal methods 25 ), they provide an approximately orthogonal or orthonormal basis that is also conditioned on frequency.…”
Section: B Implications Of the Results For Reduced Order Modelingmentioning
confidence: 99%
“…41 Having defined an acceptable number of modes, a Galerkin system of evolution equations is written for the modes in terms of advective and dissipative terms, with the latter modeled to prevent excessive energy build-up (some form of cascade is required). Approaches are inspired by an eddy-viscosity approach, 41 with more advanced closures incorporating linear approximations to the nonlinear terms 67 or nonlinear interactions directly, 68 and comparative analyses demonstrating the utility of these more advanced formulations. 42 While dyadic wavelet modes are locally correlated at singularities (providing the basis for multifractal methods 25 ), they provide an approximately orthogonal or orthonormal basis that is also conditioned on frequency.…”
Section: B Implications Of the Results For Reduced Order Modelingmentioning
confidence: 99%
“…Nonlinear models based on the Galerkin projection of filtered Navier-Stokes equations have been pursued by Wang et al (2011Wang et al ( , 2012). An approach of completely different nature is suggested by Balajewicz et al (2013). Here, no auxiliary subscale turbulence terms have been introduced in the Galerkin system, but the dissipative effects are incorporated in a generalized POD.…”
Section: Introductionmentioning
confidence: 99%
“…They generally fail, however, in the numerical simulation of convection-dominated flows [8][9][10][11][12][13][14][15]. Indeed, to ensure a low computational cost, only the first few POD modes are generally used in the ROM.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting low-dimensional ROM, however, generally yields poor results in the numerical simulation of convection-dominated flows, often in the form of numerical oscillations (see, e.g., [3,4,8,9,14,[16][17][18]). In the ROM literature, a common explanation for this failure of standard ROMs is the violation of the concept of energy cascade [3,8,9,14,18,19]. Indeed, in [20] it was shown that the concept of energy cascade is also valid in a POD setting: The main role of the neglected POD modes is to drain energy from the ROM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation